Comparison of a 10 week resistance strength training program, in muscle morphology, electromyography activity and strength gains on prepubescent girls and boys - Monteiro, A.M. (2019)
The mechanisms that are behind the strength gains, in strength training programs, are not still well evidenced. It seems to exist the certainty that strength training produces greater gains, during puberty and after, in virtue, over all, of the increase of serum testosterone, which allows an increase of muscle hypertrophy. Strength gains gotten before puberty, will be resultant of neurological adaptations, such as, the improvement of inter and intra-muscle coordination and order, the synchronization, the amount of motor units recruited, and the frequency of nervous stimulus, and not so much due to hypertrophy. The purpose of this research was to compare the maximal voluntary isometric force (MVIF), the electromyography activity (EMG) and the muscle thickness between pre-pubertal boys and girls. The results suggested that prepubescent children can increase strength following a strength training program that includes callisthenic exercises. There were no significant differences on the MVIF between boys and girls doing the triceps press exercise. The strength gains were not followed by an increase of muscle mass. In the same way, there were no significant differences according to gender on the thickness of the triceps of the both arm of the triceps. It seems that the elements underlying the increase and strength gains can be related to the increase of the coordination of the movement. The coordination seems to be an element that highly contributes to the increase of strength for more complex exercises.